Recovery of Nickel and Zinc Using Biogenerated Sulphuric Acid - Yagnentkovsky, Nadia (2009)
Sludge generated in automotive and related industries often contains heavy metals. Bioleaching is an attractive alternative for the treatment of metal containing solids. Bacteria of the genus Acidithiobacillus are the most important microorganisms applied to metal solubilisation. These microorganisms are able to produce sulphuric acid from the aerobic oxidation of elemental sulphur. The biogenerated sulphuric acid can be applied to the solubilisation of metals from a solid matrix. In this paper we present the results of our experiments aimed at the removal of nickel and zinc from sludge generated in the water treatment plant of an automotive industry. Acidithiobacillus thiooxidans cells were immobilised on sulphur pearls in a column reactor. The effects of sulphur pulp density and the dilution rate on the production of sulphuric acid were studied. In a second stage, sulphuric acid was used to solubilise the nickel and zinc from the sludge. The effects of different sludge pulp densities and initial acid pH were studied. High recoveries of zinc and nickel were obtained when the pH value of the sulphuric acid solution was lower than 2.0 for 1 and 2 % of pulp density.